2017
DOI: 10.1590/s1806-37562017000000004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact that the changes in tuberculosis treatment implemented in Brazil in 2009 have had on disease control in the country

Abstract: Objective:To analyze the impact that the 2009 changes in tuberculosis treatment in Brazil had on the rates of cure, tuberculosis recurrence, mortality, treatment abandonment, and multidrug-resistant tuberculosis (MDR-TB). Methods:An ordinary least squares regression model was used in order to perform an interrupted time series analysis of secondary data collected from the Brazilian Tuberculosis Case Registry Database for the period between January of 2003 and December of 2014. Results:The 2009 changes in tuber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 18 publications
2
21
1
1
Order By: Relevance
“…Conversely, the use of interrupted time series analysis techniques requires meeting some conditions, the most important of which being that the only change affecting the outcome measure in the period is the intervention of interest. 3 , 4 An article by Linden, 5 which was used by Rabahi et al 1 as a reference for performing interrupted time series analysis, also reinforces that caution is needed in drawing inferences when potential confounding factors, such as concomitant policies and programs, vary during the study period. It is known that, during the period studied by Rabahi et al, 1 other important changes occurred that could affect treatment outcomes, such as the lack of nationwide use of tuberculin testing within the health care system; the improvement in diagnosis, with the implementation of the Xpert MTB/RIF assay 6 ; and the economic crisis that unequally affected the population at highest risk for unfavorable treatment outcomes because of their social vulnerability.…”
Section: To the Editormentioning
confidence: 99%
See 4 more Smart Citations
“…Conversely, the use of interrupted time series analysis techniques requires meeting some conditions, the most important of which being that the only change affecting the outcome measure in the period is the intervention of interest. 3 , 4 An article by Linden, 5 which was used by Rabahi et al 1 as a reference for performing interrupted time series analysis, also reinforces that caution is needed in drawing inferences when potential confounding factors, such as concomitant policies and programs, vary during the study period. It is known that, during the period studied by Rabahi et al, 1 other important changes occurred that could affect treatment outcomes, such as the lack of nationwide use of tuberculin testing within the health care system; the improvement in diagnosis, with the implementation of the Xpert MTB/RIF assay 6 ; and the economic crisis that unequally affected the population at highest risk for unfavorable treatment outcomes because of their social vulnerability.…”
Section: To the Editormentioning
confidence: 99%
“…In the article by Rabahi et al 1 published in volume 43, issue 6, of the JBP in 2017, the authors concluded that “The changes in tuberculosis treatment [fixed-dose combination implemented by the Brazilian Ministry of Health] were unable to contain the decrease in cure rates, the increase in treatment abandonment rates, and the increase in [multidrug-resistant tuberculosis] MDR-TB rates, being associated with increased mortality from pulmonary tuberculosis during the study period.” Considering that this statement published in the major means of scientific dissemination of the Brazilian Thoracic Association may have a major impact not only on the Brazilian medical community but also on the health professionals engaged in the fight against tuberculosis, we would like this letter to be likewise published in the JBP. Some comments must be made about methodological issues that certainly influenced the conclusions of the aforementioned study.…”
Section: To the Editormentioning
confidence: 99%
See 3 more Smart Citations